2016
DOI: 10.1002/iroh.201601851
|View full text |Cite
|
Sign up to set email alerts
|

High importance of autochthonous basal food source for the food web of a Brazilian tropical stream regardless of shading

Abstract: According to the prevalent paradigm, the major source of carbon and energy for food webs of small forested streams in temperate regions is allochthonous material from the surrounding forest. Tropical streams have not been as well studied and there has been some speculation that their food webs are more aligned with in‐stream, algal production (autochthonous carbon). We studied food sources and consumers in four sites in a coastal tropical stream with gradients of 36–254 m elevation, 8–73% canopy cover and 11.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…are secondary consumers, which have as basal food source periphyton algae which usually grows on rocks. Similar results were also found in other Atlantic rainforest stream in Rio de Janeiro (Brito et al, 2006;Neres-Lima et al, 2016). We believe that is possible that these animals are using leaf accumulations as shelter during daylight hours or even that they prey on invertebrates in the litter.…”
Section: Discussionsupporting
confidence: 87%
“…are secondary consumers, which have as basal food source periphyton algae which usually grows on rocks. Similar results were also found in other Atlantic rainforest stream in Rio de Janeiro (Brito et al, 2006;Neres-Lima et al, 2016). We believe that is possible that these animals are using leaf accumulations as shelter during daylight hours or even that they prey on invertebrates in the litter.…”
Section: Discussionsupporting
confidence: 87%
“…olfersii (Decapoda: Palaemonidae) is a nocturnally active, omnivorous shrimp (Brito et al, 2006;Moulton, Souza, Silveira, & Krsulovic, 2004;Neres-Lima et al, 2016), and P. brasiliana (Decapoda: Atyidae) olfersii (Decapoda: Palaemonidae) is a nocturnally active, omnivorous shrimp (Brito et al, 2006;Moulton, Souza, Silveira, & Krsulovic, 2004;Neres-Lima et al, 2016), and P. brasiliana (Decapoda: Atyidae)…”
Section: Study Organismsmentioning
confidence: 99%
“…is an herbivorous shrimp (Neres- Lima et al, 2016) that is typically active during the day (P. Oliveira-Cunha personal observation).…”
Section: Study Organismsmentioning
confidence: 99%
“…However, several studies have found surprisingly high levels of autochthony (i.e., aquatic diet) in smallstream consumers, despite low incident light and high allochthonous inputs (McCutchan & Lewis, 2002;Neres-Lima et al, 2016;Stenroth et al, 2015;Brett et al, 2017). This deviation from predictions occurs presumably because stream autotrophic productioneven if occurring at low levels-is a much better resource than terrestrially derived organic matter, and would therefore, be favored by stream consumers (Brett et al, 2017).…”
Section: Introductionmentioning
confidence: 97%